Gut microbial community structure of the adult citrus root weevil Diaprepes abbreviatus - Rodriguez-Fernandez, Imilce A.; Santiago-Rodriguez, Tasha M.; Figueroa-Pratts, Paola G.; Cintrón-Berríos, Keislamarí; Rodriguez-Cornier, Nichole D.; Toranzos, Gary A. (Frontiers in Insect Science, 2025)
Diaprepes abbreviatus is an agricultural pest known to affect around 270 plant species across the Caribbean and the United States, posing significant challenges to pest management. Chemical control dominates management, but environmental and health concerns motivate microbiome-informed alternatives. However, limited information exists on the gut anatomy, physicochemical environment, and microbial composition of D. abbreviatus. In this study, we provide the first comprehensive characterization of the gut morphology, pH, and microbiota of adult D. abbreviatus in both females and males collected in Puerto Rico. Using dye-based gut tracing, we identified foregut, midgut, and hindgut or posterior gut compartments, and confirmed the presence of a muscular, sclerotized gizzard. Colorimetric analysis revealed a mildly acidic gut environment (approximately pH 4–5, based on qualitative ranges), consistent across sexes and regions. Shotgun metagenomic sequencing of dissected guts from males and females revealed microbial communities distinct from the leaf samples microbiota. While alpha and beta diversity did not differ significantly between sexes, co-occurrence analyses identified sex-specific correlation patterns among bacterial taxa. Notably, Enterobacter cloacae, Pantoea vagans, Lactococcus lactis, and Pseudomonas monteilii were repeatedly detected across individuals and generated metagenomic datasets, and some were localized to the hindgut, suggesting possible niche specialization. The presence of taxa, such as Enterobacter cloacae, previously reported as symbionts in other phytophagous insects further supports the hypothesis that certain bacteria may contribute to host digestion or adaptation. These findings establish a framework for understanding the gut environment and microbial community of D. abbreviatus, and highlight candidate taxa for future functional studies. More broadly, this work supports further research into the potential roles of gut microbiota in the ecology and management of this pest.